RESERVATION SYSTEM IN THE DISTRIBUTION OF GOODS IN PT.BWI CANNED FOOD - Kenya Puspita Lindri; Ir. Ire Puspa Wardhani (Jurnal Sistem Informasi, 1998)
The approach will be required once for easy file storage that is often lost due tonegligence someone, good sequencing data search will be easy to get used to aminimum so that the time may be achieved.Used documents can be used with the best when dperlukan later and once thenecessary computer for easy data storage process of data validity can be guaranteedwell.